In situ encapsulation of pyridine-substituted tetraphenylethene cations in metal–organic framework for the detection of antibiotics in aqueous medium. Issue 27 (25th June 2019) - Ying, Yan-Mei; Tao, Chen-Lei; Yu, Maoxing; Xiong, Yi; Guo, Chang-Rui; Liu, Xun-Gao; Zhao, Zujin
Abstract : A highly luminescent MOF containing tetraphenylethene-based cations has been prepared through in situ encapsulation, which can serve as a fluorescent sensor for selective and sensitive detection of nitrofuran antibiotics in aqueous media. Abstract : Antibiotics have become a pollutant in water due to their abuse, which poses a threat to the environment and human health. An urgent and meaningful task is to develop highly sensitive and selective sensors. Herein, a new and simple luminescent MOF [Zn8 (C5 H4 N5 )4 (C14 H8 O4 )6 O(C50 H44 N4 )0.5 ] (TMPyPE@bio-MOF-1) was synthesized by in situ encapsulation of cationic TPE-based guest TMPyPE into an anionic MOF. TMPyPE@bio-MOF-1 exhibits high stability and strong fluorescence in water, and can selectively and sensitively detect nitrofuran antibiotics in aqueous medium. At the same titration concentration, TMPyPE@bio-MOF-1 shows higher fluorescence quenching efficiencies of 96% for NFZ and 95.5% for NFT compared with other antibiotics, which can be detected by the naked eye. Due to the simplicity and sensitivity of analysis, the tetraphenylethene-based luminogen encapsulated LMOF material reported would have wide application potential in environmental pollution analysis.